2021
DOI: 10.1186/s40663-021-00353-5
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning tree water usage into storage and transpiration in a mixed forest

Abstract: Background Water migration and use are important processes in trees. However, it is possible to overestimate transpiration by equating the water absorbed through the plant roots to that diffused back to the atmosphere through stomatal transpiration. Therefore, it is necessary to quantify the water transpired and stored in plants. Method The δ2H/δ18O technique and heat ratio method were used to explore the water usage of coniferous and broad-leaved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
1
19
0
1
Order By: Relevance
“…Cd-contaminated soil concentrations of 5 and 20 mg Cd kg −1 were selected because they were beneficial to plant growth with a high BCF value. In addition, these two Cd concentrations have been reported as common Cd-contaminated levels in the Dabao mountain area in Guangdong province, China [10]. The model calculation shows that B. pekinensis is more effective than B. juncea to clean up soil with either an initial concentration of 5 or 20 mg Cd kg −1 .…”
Section: Potential Phytoremediation Of Moderate Cd-contaminated Soil By B Juncea and B Pekinensismentioning
confidence: 92%
See 3 more Smart Citations
“…Cd-contaminated soil concentrations of 5 and 20 mg Cd kg −1 were selected because they were beneficial to plant growth with a high BCF value. In addition, these two Cd concentrations have been reported as common Cd-contaminated levels in the Dabao mountain area in Guangdong province, China [10]. The model calculation shows that B. pekinensis is more effective than B. juncea to clean up soil with either an initial concentration of 5 or 20 mg Cd kg −1 .…”
Section: Potential Phytoremediation Of Moderate Cd-contaminated Soil By B Juncea and B Pekinensismentioning
confidence: 92%
“…In order to better simulate the adsorption of heavy metals by plants under natural environmental conditions, a pot culture experiment was conducted at seven soil levels (D.W) (5,10,20,40,60, 80 and 100 mg kg −1 of Cd) by applying non-polluted agriculture soil spiked with a CdCl 2 •2.5 H 2 O solution and an unamended control for comparison. We sprinkled the solution into the soil and left it for a month for equilibration.…”
Section: Design Of Pot Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, global climate observations demonstrated that land warms faster at night than during the day, and this trend can lead to an increase in plant water requirement at night ( Zeppel et al, 2015 ). The nighttime sap flow movement in plants can facilitate the transport of nutrients and oxygen for plant growth, which in turn affects plant growth status and productivity ( Chen et al, 2020b ; Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%